Sirolimus improves seizure control in pediatric patients with tuberous sclerosis: A prospective cohort study. (July 2020) - He, Wen; Chen, Jian; Wang, Yang-Yang; Zhang, Meng-Na; Qian-Lu; Wang, Qiu-Hong; Luo, Xiao-Mei; Chen, Xiao-Qiao; Zou, Li-Ping
Highlights: Sirolimus has a significant effect on seizures associated with tuberous sclerosis. Early use of sirolimus to control seizures can bring long-term benefits. The overall tolerability of sirolimus is acceptable. Abstract: Purpose: This study aimed to analyze the therapeutic effect of sirolimus on seizures in pediatric patients with tuberous sclerosis. Methods: We first compared the efficacy of controlling seizures in all patients after they had taken sirolimus for one year, and then we performed a subgroup analysis based on whether the administered antiepileptic drugs were changed to determine whether the efficacy was associated with changes of antiepileptic drugs. Results: A total of 91 eligible children were enrolled. The response rate was 78.0 % (71/91), and 47.2 % (43/91) of all patients were became seizure-free. The improvement in seizure control before and after treatment with sirolimus was significant ( p  < 0.001). In the AEDs unaltered group, 34 were responders (34/45, 75.6 %, 95 % CI 17.4–88.3), of which 24 were seizure-free (24/34, 70.6 %). In the AEDs-altered group, 37 were responders (37/46, 80.4 %, 95 % CI 56.7–88.1), of which 19 were seizure-free (19/37, 51.4 %). There was no significant difference between the two groups for reductions in rate of seizure frequency ( p  = 0.308). In the patients with refractory epilepsy, treatment with sirolimus was also effective ( p  = 0.01). Logistic regression analysis showed that age was an important factor affecting outcome of epilepsy ( p = 0.003, 95 % CI 2.05–38.31). No Grade 3 or 4 adverse events were noted during the follow-up. Conclusions: Sirolimus has a significant effect on seizures associated with tuberous sclerosis complex (TSC), with no or only moderate adverse events after long-term administration. Sirolimus could be used as the first-line medication for pediatric patients with TSC-associated epilepsy.